There is No Bad Religion. There are Only Bad People - Um-e-Rubbab; Muhammad Irshad; Sana Aroos Khattak (Journal of Management Practices, Humanities and Social Sciences, 2021)
Religious diversity has become an important issue for organizations. Religious diversity brings many challenges for managers and HR policymakers. Organizations cannot overrule the chances of religious harassment. Pakistani organizations are highly diverse, with a workforce of various religious backgrounds. The objective of this study was to find out the role of hatred as an antecedent and perceived workplace exclusion as an outcome for religious harassment among employees of public and private sector organizations. Con- firmatory factor analysis was performed for validation of factor structure. Convenience sampling, a non-random sampling technique, was used for data collection, and the size of the sample was determined by G*Power (Hair et al., 2014). Using the SEM method, we tested our model's hypothesis with three hundred and ninety-eight employees. Results have shown expected associations between study constructs, such that hatred was found significantly correlated with religious harassment, and religious harassment was significantly correlated to workplace exclusion. In comparison, religious harassment mediated the relationship between hatred and workplace exclusion. Organizations need to address the issue by fabricating a religiously diverse culture with suitable policies and training. By proposing that the negative emotion landscape can trigger a range of socially undesirable outcomes, we tried to highlight the research that may benefit employers, and findings extend to understand context-specific concepts of perceived workplace exclusion. Religious harassment negatively influences employees and the workplace climate. It has severe repercussions for the repute of organizations.